Collaborative governance of tropical landscapes - Colfer, C.J.P.; Pfund, J.L. (Earthscan, 2011)
This book provides a novel approach to governance relating to biodiversity and human well-being in complex tropical landscapes, including forests and protected areas. It focuses attention at the interface between communities and the landscape level, building on interdisciplinary research conducted in five countries (Cameroon, Indonesia, Laos, Madagascar and Tanzania). In each country, the research was set within the framework of a major national policy thrust. The book improves our understanding of and ability to manage complex landscapes---mosaics of differing land uses---in a more adaptive and collaborative way that benefits both the environment and local communities. It includes both single country and cross-site analyses, and focuses on themes, such as resettlement, land use planning, non-timber forest product use and management, the disconnect between customary and formal legal systems, and the role of larger scale policies in local level realities. Chapters also analyze experience with monitoring and a local governance assessment tool. The work also provides guidance for those interested in management and governance at lower and intermediate levels (village, district), scales likely to grow in importance in the global effort to mitigate and adapt to climate change.